1977
DOI: 10.1002/aja.1001500202
|View full text |Cite
|
Sign up to set email alerts
|

A study by light and scanning electron microscopy of the lining epithelium of the guinea pig bladder following artificial ulceration

Abstract: Following artificial ulceration of the guinea pig bladder epithelium, study by light microscopy showed that mitotic activity occurs within 24 hours in the basal layer of the remaining epithelium; which leads to thickening, disorganization and cell shedding. At the ulcer margin, the epithelium forms a rolled edge, from the extremity of which a two-layered sheet of flat cells grows over the edematous ulcer bed, and the ulcer site is protected during dilation of the bladder by localized muscle spasm. Healing is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
2

Year Published

1981
1981
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
2
9
0
2
Order By: Relevance
“…Pre sumably, fusion of the microvilli, together with the linkage of the rows, produces the reticular pattern of ridges. A similar se quence was observed in new cells, formed after artificial ulceration of the bladder epithelium [Wong and Martin, 1977b], It may therefore be concluded that the mat uration of the surface cells in the fetus is similar to that observed in the new cells formed after injury in the adult.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Pre sumably, fusion of the microvilli, together with the linkage of the rows, produces the reticular pattern of ridges. A similar se quence was observed in new cells, formed after artificial ulceration of the bladder epithelium [Wong and Martin, 1977b], It may therefore be concluded that the mat uration of the surface cells in the fetus is similar to that observed in the new cells formed after injury in the adult.…”
Section: Discussionsupporting
confidence: 58%
“…However, since the same process occurs in adult transi tional epithelium when mitotic activity is stimulated, either by acute distension of the bladder [Martin, 1972] or by artificial ulcer ation [ Wong and Martin, 1977b], it is sug gested that it results from overproduction and consequent overcrowding of cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others differ entiate between microvilli and microplicae or ridges [Wong and Martin, 1977;Mills and Malick, 1978;Hodgkins et al, 1978: Pfister andRenner, 1978;Malczak, 1980]. In the conjunctival epithelium of domestic ruminants we were able to clearly find two types of cyto plasmic projections.…”
Section: Discussionsupporting
confidence: 53%
“…In the urinary bladder epithelium, Wong and Martin [1977] found microvilli on immature surface cells, and microplicae in mature cells. The same authors postulate that microplicae originate from microvilli that have grown together.…”
Section: Discussionmentioning
confidence: 99%